Gorenc, Klaus Dieter (1999). Alter, Revista Internacional de Teoría, Filosofía y Sociología del Derecho, 3 (7, 8, 9). Campeche, México: Centro de Investigaciones Jurídicas de la Universidad Autónoma de Campeche, 568 p. - Llanos Zuloaga, Roberto (2002)
No contiene resumen